Three-Dimensional Pre-Bent Titanium Implant for Concomitant Orbital Floor and Medial Wall Fractures in an East Asian Population - Lee, Kyung Min; Park, Ji Ung; Kwon, Sung Tack; Kim, Suk Wha; Jeong, Eui Cheol (Archives of Plastic Surgery, 2014)
Background The objective of this article is to evaluate clinical outcomes of combined orbital floor and medial wall fracture repair using a three-dimensional pre-bent titanium implant in an East Asian population.Methods Clinical and radiologic data were analyzed for 11 patients with concomitant orbital floor and medial wall fractures. A combined transcaruncular and inferior fornix approach with lateral canthotomy was used for the exposure of fractures. An appropriate three-dimensional preformed titanium implant was selected and inserted according to the characteristics of a given defect.Results Follow-up time ranged from 2 to 6 months (median, 4.07 months). All patients had a successful treatment outcome without any complications. Clinically significant enophthalmos was not observed after treatment.Conclusions Three-dimensional pre-bent titanium implants are appropriate for use in the East Asian population, with a high success rate of anatomic restoration of the orbital volume and prevention of enophthalmos in combined orbital floor and medial wall fracture cases.
Keywords: Orbital fractures; Enophthalmos; Orbital implant